A Study of Development In the Condition of Children Who Work In Different Industries In India: Formulating integrated approaches and intervention strategies towards eradicating child labor in India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Engaging children in any sort of work inhibits affectstheir fullest growth. Legislative provisions are formulated to prevent themenace of child labor. But the children are the most deprived section ofpopulation forced to earn a pittance or to contribute to family worksacrificing personal development. Poverty coupled with rapidly growingpopulation, ignorance and increasing dependency load are behind the grimincidence of children employment in the villages and towns of developingcountries. Though Indiais signatory of various international Conventions and Agreements, there isgrowing number of child labour in India. They work under veryhazardous conditions. Given the magnitude and complexity of the problem, thisarticle is an attempt to formulate integrated approach and various interventionstrategies towards eradication of the problem of child labour.